Effect of nanoliposomal entrapment on antioxidative hydrolysates from goose blood protein. Issue 10 (31st August 2020) - Huang, Jin; Wu, Mengting; Yang, Kun; Zhao, Manman; Wu, Di; Ma, Jing; Ding, Baomiao; Sun, Weiqing
Abstract: In this study, the encapsulation of goose blood hydrolysate (GBH) was performed within nanoliposomes. We investigated the physicochemical properties, stability, antioxidant indices, the morphology of nanoparticles, the digestion stability in simulated gastrointestinal fluid, differential scanning calorimetry (DSC) analysis, and Fourier transform infrared (FTIR) spectroscopy. GBH was successfully encapsulated into nanoliposomes using reverse‐phase evaporation method. The entrapment efficiency of GBH‐loaded nanoliposomes was about 70.99 ± 2.85%, the average particle size was 93.3 ± 2.45 nm, the zeta‐potential of GBH‐loaded nanoliposomes was −30 mV, and the morphology of GBH‐loaded nanoliposomes was characterized by transmission electron microscope. Moreover, the results of DSC and FTIR showed that the GBH nanoliposome was more stable than the empty liposomes due to hydrogen bond complexation between liposome and GBH. The release of GBH from nanoliposomes could be significantly controlled, and the release ratios were 48.9 ± 2.96% in simulated gastric fluid and 59.9 ± 5.30% in simulated intestinal fluid, respectively, proving that degradation rate of antioxidant activities of GBH encapsulated in nanoliposomes was decreased. In conclusion, nanoliposomes embedding is a promising and effective way to increase the stability of hydrolysates from GBH and produce various types of functional food.